ISSUES IN TEACHING ENGLISH IN A CULTURAL CONTEXT: A CASE OF INDONESIA - Suryanto Suryanto (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2014)
Abstract: The significant role of English in the global era triggers many countries to make policies to include English as compulsory subjects for their citizen. However, the existing culture in every country is not necessarily in tandem with the culture that is embedded in English language. This condition may raise many issues that can hamper the teaching-learning process. Through literary studies, this paper explores how English language teaching-learning takes place in Indonesian cultural context and find the issues hampering students to learn English. Among the hampering issues are students’ characteristics, teacher factor, norm and belief, and some language aspects of English. Key words: Culture, norms, belief, English language teaching, language aspects